Biochemical and functional characterization of Mycobacterium tuberculosis ketol-acid reductoisomerase. Issue 9 (13th September 2021) - Singh, Nirbhay; Chauhan, Anu; Kumar, Ram; Singh, Sudheer Kumar
Abstract : Branched-chain amino acids (BCAAs) are essential amino acids, but their biosynthetic pathway is absent in mammals. Ketol-acid reductoisomerase (IlvC) is a BCAA biosynthetic enzyme that is coded by Rv3001c in Mycobacterium tuberculosis H37Rv ( Mtb- Rv) and MRA_3031 in M. tuberculosis H37Ra ( Mtb- Ra). IlvCs are essential in Mtb- Rv as well as in Escherichia coli . Compared to wild-type and IlvC-complemented Mtb -Ra strains, IlvC knockdown strain showed reduced survival at low pH and under low pH+starvation stress conditions. Further, increased expression of IlvC was observed under low pH and starvation stress conditions. Confirmation of a role for IlvC in pH and starvation stress was achieved by developing E. coli BL21(DE3) IlvC knockout, which was defective for growth in M9 minimal medium, but growth could be rescued by isoleucine and valine supplementation. Growth was also restored by complementing with over-expressing constructs of Mtb- Ra and E. coli IlvCs. The E. coli knockout also had a survival deficit at pH=5.5 and 4.5 and was more susceptible to killing at pH=3.0. The biochemical characterization of Mtb- Ra and E. coli IlvCs confirmed that both have NADPH-dependent activity. In conclusion, this study demonstrates the functional complementation of E. coli IlvC by Mtb- Ra IlvC and also suggests that IlvC has a role in tolerance to low pH and starvation stress.